2007
DOI: 10.1002/hbm.20397
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity mapping using the ferromagnetic Potts spin model

Abstract: An unsupervised stochastic clustering method based on the ferromagnetic Potts spin model is introduced as a powerful tool to determine functionally connected regions. The method provides an intuitively simple approach to clustering and makes no assumptions of the number of clusters in the data or their underlying distribution. The performance of the method and its dependence on the intrinsic parameters (size of the neighborhood, form of the interaction term, etc.) is investigated on the simulated data and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…These observations indicate that there is a vast region in the bandwidth-temperature space for which good clustering results may be found. This has already been observed by Stanberry, Murua, and Cordes (2008) on fMRI data, and has been suggested by Blatt, Domany, and Wiseman (1996) as a result of what is known about the Potts model in ferromagnetism. Note from Table 3 that the optimal temperature for the SPMC is sometimes very low.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These observations indicate that there is a vast region in the bandwidth-temperature space for which good clustering results may be found. This has already been observed by Stanberry, Murua, and Cordes (2008) on fMRI data, and has been suggested by Blatt, Domany, and Wiseman (1996) as a result of what is known about the Potts model in ferromagnetism. Note from Table 3 that the optimal temperature for the SPMC is sometimes very low.…”
Section: Discussionsupporting
confidence: 65%
“…Stanberry, Murua, and Cordes (2008) observed that these regions are also stable regions for the number of clusters and may correspond to phase-free regions of the random cluster model (i.e., no giant component appears in these regions; see Section 4.1.1). Very often in our experiments, the informative data-driven prior maximizer (σ p , T p ) lies in the high-density region of the posterior, and the clustering evidence is similar for both choices of the parameters: the MAP estimates and the informative prior maximizer.…”
Section: The Informed Conditional-potts Clusteringmentioning
confidence: 93%
See 2 more Smart Citations
“…Reichardt and Bornholdt (2004) introduced a spin glass Hamiltonian with a global diversity constraint to identify probable community assignments in complex networks. Stanberry, Murua, and Cordes (2007) applied the method to study functional connectivity patterns in fMRI data and examined the dependence of the method on neighborhood structure, signal-to-noise ratio, and spatial dependence in the data. Potts model clustering has been applied to different fields such as computer vision (Domany et al 1999), gene expression data (Getz et al 2000;Einav et al 2005), high-dimensional chemical data (Ott et al 2004(Ott et al , 2005 and neuronal spike detection (Quiroga, Nadasdy, and Ben-Shaul 2004).…”
Section: Maximizing (13) Is Equivalent To Minimizingmentioning
confidence: 99%